Controller and scheduler codesign for feedback control over IEEE 802.15.4 networks - Peters, E. G. W.; Quevedo, D. E.; Fu, M. (Trans. Contr. Syst. Technol.)

Discrete-time hands-off control by sparse optimization - Nagahara, M.; stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Robust stability of a class of Networked Control Systems - Lješnjanin, M.; Nešić, D.; Quevedo, D. E. (Automatica)

Kalman Filtering With Relays Over Wireless Fading Channels - Leong, A. S.; Quevedo, D. E. (Trans. Automat. Contr.)

Characterization of maximum hands-off control - Chatterjee, D.; Nagahara, M.; Quevedo, D. E.; Rao, K. S. M. (Syst. & Contr. Lett.)

Predictive control, embedded cyberphysical systems and systems of systems – A perspective - Lucia, S.; Kögel, M.; Zometa, P.; Quevedo, D. E.; Findeisen, R. (Annual Reviews in Control)

On Network Topology Reconfiguration for Remote State Estimation - Leong, A. S.; Quevedo, D. E.; Ahlén, A.; Johansson, K. H. (Trans. Automat. Contr.)

Mehrphasige ph ̈anomenologische sowie mehrskalige mikroskopische Modellierung von Phasenumwandlungen in einem Hybridumformprozess - Schneidt, Andreas

Rezension zu Brinkmann, Erika (Hrsg.): Rechtschreiben in der Diskussion. Schriftspracherwerb und Rechtschreibunterricht (= Beiträge zur Reform der Grundschule 140) Bad Langensalza: Beltz. 318 S. - Blachut, Alisa (Grundschulunterricht Deutsch)

Plants as Digital Things - Alpsancar, Suzana (Tecnoscienza. Italian Journal of Science & Technology Studies)
Seeds have traditionally been collected according to their reproductive cycles, i.e. the time when they lose their potential of becoming a real plant. Therefore, the locations of botanic gardens or seed banks imply the vicinity of agricultural land. This article exemplifies the transformation of plant collections into gene and data banks by investigating the Svalbard Global Seed Vault (SGSV) in Norway and the German Genebank for Fruit Crops (DGO). It shows that international efforts to safeguard biodiversity by intertwining them with bioinformatics infrastructure transform seeds and other plant genetic material into digitalized objects. The almost virtual genetic material, now stored without the neighborhood of acres or gardens, is, at the same time, seen as “options” for new high-tech plants, which might be transplanted to a future territory. Consequently, plant varieties are circulating around the globe in form of genetic material and data. The article shows that the digitalization induces a specific distinction between the material and the digital flows of plants.

Einfluss von Mixed-Mode-Beanspruchung auf das Ermüdungsrisswachstum in Bauteilen und Strukturen - Eberlein, Alexander

A Linear Time Algorithm for Quantum 2-SAT - de Beaudrap, Niel; Gharibian, Sevag (Proceedings of the 31st Conference on Computational Complexity (CCC 2016))
The Boolean constraint satisfaction problem 3-SAT is arguably the canonical NP-complete problem. In contrast, 2-SAT can not only be decided in polynomial time, but in fact in deterministic linear time. In 2006, Bravyi proposed a physically motivated generalization of k-SAT to the quantum setting, defining the problem "quantum k-SAT". He showed that quantum 2-SAT is also solvable in polynomial time on a classical computer, in particular in deterministic time O(n^4), assuming unit-cost arithmetic over a field extension of the rational numbers, where n is number of variables. In this paper, we present an algorithm for quantum 2-SAT which runs in linear time, i.e. deterministic time O(n+m) for n and m the number of variables and clauses, respectively. Our approach exploits the transfer matrix techniques of Laumann et al. [QIC, 2010] used in the study of phase transitions for random quantum 2-SAT, and bears similarities with both the linear time 2-SAT algorithms of Even, Itai, and Shamir (based on backtracking) [SICOMP, 1976] and Aspvall, Plass, and Tarjan (based on strongly connected components) [IPL, 1979].
Keywords: quantum 2-SAT; transfer matrix; strongly connected components; limited backtracking; local Hamiltonian

Entwicklung einer Methodik zur Simulation der Lebensdauer von Klebverbindungen mit Polyurethan-Klebstoffen - Kaßner, Martin

Qualifizierung des Reibelementschweißens von ultrahochfesten Aluminium-Silizium-beschichteten Stahlblechwerkstoffen für den Karosseriemischbau - Olfermann, Thomas Ernst Christian

Qualifizierung von PU-Klebstoffen für den Einsatz auf lackierten Oberflächen (semi-)struktureller und crashrelevanter Strukturen eines Automobils - Beck, Alexander

Entwicklung eines impulsartig und butzenfrei eingetriebenen Elementes für das Widerstandsschweißen von Aluminium-Stahl-Verbindungen - Hartwig-Biglau, Sergej

Weiterentwicklung der mechanischen Fügetechnik zum vorlochfreien Fügen von Faser-Kunststoff-Verbunden im Automobilkarosseriebau - Rothe, Kevin

Beitrag zur experimentellen und simulativen Beschreibung der Delaminations-Initiierung an bauteilnahen Faserverbund-Geometrien - Frede, Daniel

Weiterentwicklung des Widerstandselementschweißens für den Einsatz in der automobilen Serienfertigung - Meyer, Christoffer

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet - Fuchs, Christian